Providing reproductive health services for women who inject drugs: a pilot program - Lauren Owens; Kelly Gilmore; Mishka Terplan; Sarah Prager; Elizabeth Micks (BMC, 2020)
Abstract Background Needle syringe programs (NSPs), a proven harm reduction strategy for people who inject drugs, frequently offer limited healthcare services for their clients. Women who inject drugs face multiple barriers to accessing reproductive health care in traditional settings: personal histories of trauma, judgmental treatment from providers, and competing demands on their time. Our aim was to implement patient-centered reproductive healthcare services at a Seattle NSP. Methods We interviewed clients and staff of an NSP in Seattle and staff of other community-based organizations serving women who inject drugs, then used the Consolidated Framework for Implementation Research to code transcripts deductively. Based on our qualitative work, we implemented reproductive health care at the NSP program 1 day per week. We evaluated the implementation by surveying staff and clients and auditing charts over a 9-month period. Results Clients and staff (N = 15 for clients, N = 13 for staff) noted a high unmet need for trauma-informed, accessible reproductive health care. We successfully implemented reproductive health care services including short- and long-acting contraception, sexually transmitted disease testing, and cervical cancer screening. Survey data was limited but demonstrated client satisfaction with services. Conclusions Integrating reproductive health care into an NSP's clinical services is feasible and can be a source of low-barrier preventive care for women unable to seek gynecologic care elsewhere.